COMMENTS ON THE STATEMENT OF ACCOUNTING PRINCIPLES. - Sanders, T. H. (The Accounting Review, 1937)
Abstract The article discusses the statement of accounting principles, published in the June 1936 issue of the journal The Accounting Review. It involves the entire question of income determination, the most fundamental of all accounting problems. In the first place earnings, earned surplus, capital surplus, and capital represent important conceptions which are necessary to be kept distinct, in spite of the constant interchange among them. Changes in the accounts representing these four different things should accordingly be kept equally distinct. The income statement should be marked off in three stages showing income of the year, income adjustments for prior years, and realized capital gains and losses. Second, corrections of the costs and income of past years are not costs and income of this year. Earned surplus is the account containing the present resultant of all past income charges and credits, and it is the account to be used for subsequent corrections therein. Third, substantial capital losses and gains are certainly not proper items for the income account of any year. It is necessary to be clear at the outset that they really are capital losses and gains.